Optimized Extraction of Two Organic Acids from Herba artemisiae scopariae with Reversed-Phase High Performance Liquid Chromatography Separation - Lee, Y.R.; Tian, M.; Row, K.H. (Asian Journal of Chemistry, 2012)
Extraction of chlorogenic acid and caffeic acid from Herba artemisiae scopariae was developed by liquid-liquid extraction with liquid chromatography separation. By utilizing different extraction solvents, extraction time and extraction temperature, the optimum extraction conditions were established. The extract was separated by a C18 column with a mobile phase consisting of acetonitrile-water (20:80, v/v). 4.78 mg/g of chlorogenic acid and 0.26 mg/g of caffeic acid were obtained. This method is simple and sensitive and has been applied successfully to determine the component of chlorogenic acid and caffeic acid in Herba artemisiae scopariae.